2021
DOI: 10.54203/scil.2021.wvj61
|View full text |Cite
|
Sign up to set email alerts
|

Milk Production and Reproductive Performance of Retained and Culled Cows in a Large Holstein Herd in Egypt

Abstract: The study aimed to identify the culling reasons of Holstein cows raised in a large commercial herd in Egypt with emphasis on the performance of retained and culled cows. A total of 31534 complete lactation records for 10994 cows calved from 2008 to 2019 were used. The overall rate of culling per lactation was 61.1%. Involuntary culling represented 92% of all culling cases. The reasons for culling included mastitis and udder problems (24.2%), reproductive disorders (18.7%), metabolic and digestive disorders (13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Rilanto et al (2020) further observed 26.24% culling rate in Estonian dairy cows. High overall culling rate per lactation with 61.1% was observed by Fahim et al (2021). Lower overall culling rate of 17.38% in Kankrej cattle was reported by Madhavatar et al (2019).…”
Section: Resultsmentioning
confidence: 69%
“…Rilanto et al (2020) further observed 26.24% culling rate in Estonian dairy cows. High overall culling rate per lactation with 61.1% was observed by Fahim et al (2021). Lower overall culling rate of 17.38% in Kankrej cattle was reported by Madhavatar et al (2019).…”
Section: Resultsmentioning
confidence: 69%
“…The lowest values of longevity and PL were recorded by Cows cows culled due to endemic diseases recorded the lowest values of longevity, therefore they recorded the lowest LTMY in this study (28809 kg). This is because the highest proportion of these cows were culled in the first lactation [27] and PL, they were lesser than the overall mean by 5.8% and 7.8%. So they recorded the lowest LTMY (28809 kg) which was lower than the overall mean by 4.6%.…”
Section: All Of These Current Resultsfindings Reflect the Risk Of Keeping Cows Having Reproductivementioning
confidence: 93%